Comparative study of synthesis methods and electrochemical performance of nickel molybdate (NiMoO4) nanostructures for supercapacitor applications - S. Sakthivel; S. Shobika; A. Dinesh; K. Yogalakshmi; R. Suriyaprakash; B. Kabilan; P. Sathyajith; Sampath Elumalai; Lalitha Gnanasekaran; Manikandan Ayyar; M. Santhamoorthy (Results in Chemistry)
This study investigates the comparative synthesis methods and electrochemical performance of nickel molybdate (NiMoO4) nanoparticles, focusing on their potential applications in supercapacitors. Nickel molybdate nanoparticles were synthesized using co-precipitation and microwave combustion methods. Comprehensive characterization techniques, including UV-DRS, XRD, FT-IR, PL, SEM, and TGA, were employed to analyse the structural, optical, morphology and thermal properties of the samples. Electrochemical evaluations revealed that the co-precipitated nanoparticles (NMCP) exhibited a specific capacitance of 168 F g−1 at a current density of 1 A g-1. In contrast, the microwave-combusted nanoparticles (NMMC) demonstrated superior performance with a specific capacitance of 224 F g−1 at the 1 A g-1 current density. These findings indicate that the microwave combustion method produces nickel molybdate nanoparticles with enhanced electrochemical performance, making them more suitable for high-performance supercapacitor applications.